Pembuatan Nata De Coco di Nagari Kamang Hilir Kabupaten Agam Sebagai Upaya Pemberdayaan Masyarakat - Hasnah Ulia; Apsari Puspita Aini; Enny Nurmalasari; Miftahul Khairati; Muhammad Zulfikar Luthfi; Agung Kurnia Yahya (Journal of Industrial Community Empowerment, 2023)
Agam district has a coconut plantation of 56,744 hectares with an average production of 3,000 tons per year. Coconut water is one of the coconut plant products that has not been utilized optimally. Many benefits or new products that have a higher selling value use coconut water as a raw material. One of the products derived from coconut water that we consume daily is Nata de coco. Nata de coco has high fiber, but low in calories. Nata de coco can also be a business opportunity for the home industry. Based on the business opportunity from Nata de coco, The community service of Politeknik ATI Padang held the training of the production of Nata de coco to the women community in Kamang Hilir Village, Agam District, West Sumatera. The training was carried out on February 5, 2023 attended by 30 participants. The training began with the explanation about the materials and tools used in making Nata de coco. The main materials used were coconut water, urea, sugar, Acetobacter xylinum. Then, the practice is carried out jointly between the women community and the community service team from Politeknik ATI Padang. The training was closed with the presentation of business prospective from Nata de coco. All of the participants were enthusiastic with this training. It is expected that the women community in Kamang Hilir Village have the knowledge and the skill to make their own Nata de coco.